Complications related to transhepatic venous access in the catheterization laboratory—A single center 12‐year experience of 124 procedures. Issue 1 (21st March 2014) - Qureshi, Athar M.; Prieto, Lourdes R.; Bradley‐Skelton, Sharon; Latson, Larry A.
<x xml:space="preserve">Abstract</x> Objectives To identify complications and measures that can be undertaken to prevent complications from transhepatic central venous access. Background Utility and safety data from a large experience of patients undergoing transhepatic venous access are lacking. Methods The records of patients who underwent transhepatic venous access between June 2000 and October 2012 at The Center for Pediatric and Congenital Heart Disease at The Cleveland Clinic were reviewed. Results One hundred twenty‐four transhepatic procedures were performed in 81 patients. The median weight of the patients was 6.3 (2.2–94) kg at a median age of 7 months (2 weeks to 35 years). Diagnostic catheterizations were performed in 75, interventions in 39, and central venous line placement in 91 procedures. The median maximum sheath size inserted was 8 (4–14) French. There were 10 (8%) major adverse events in 8 procedures—bleeding related (n = 6 with 1 death as a result) or complete heart block with instability or requiring intervention (n = 4). Heart block persisted after the catheterization in three patients (2 days, 2 weeks, 1 month). Minor adverse events (transient heart block) occurred in 5 (4 %) procedures. Weight, age, and French size of sheath (P = 0.46, 0.84, and 0.18) were not associated with complications. In addition, time to gain access was not different between non‐complicated and complicated cases (median 19.5 versus 15.1 min, P = 0.72). Diagnostic and interventional procedures were not associated with more complications compared with procedures involving central venous line placement alone (P = 0.5). Conclusions Transhepatic access is an extremely useful modality of access to the heart and vascular structures in some patients with complex heart disease. Prevention of complications should focus on minimizing bleeding risks and heart block. © 2013 Wiley Periodicals, Inc.